Lower limb joint loading in patients with unilateral hip osteoarthritis during bipedal stance and the effect of total hip replacement - van Drongelen, S.; Holder, J.; Stief, F. (Frontiers in Bioengineering and Biotechnology, 2023)
Osteoarthritis of the hip is a common condition that affects older adults. Total hip replacement is the end-stage treatment to relief pain and improve joint function. Little is known about the mechanical load distribution during the activity of bipedal stance, which is an important daily activity for older adults who need to rest more frequently. This study investigated whether pathological hip and knee joint moments occur during bipedal stance in patients with unilateral hip osteoarthritis and how the distribution changes one year after total hip replacement. Kinematic and kinetic data from bipedal stance were recorded. External hip and knee adduction moments were calculated and load distribution over both limbs was calculated using the symmetry angle. Preoperatively, the non-affected limb carried 10% more body weight than the affected limb when standing on two legs. Moreover, the mean external hip and knee adduction moments of the non-affected limb were increased compared to the affected limb. At follow-up no significant differences were observed between the patients’ limbs. Preoperative and postoperative changes in hip adduction moment were mainly explained by the combination of the vertical ground reaction force and the hip adduction angle. Stance width also explained changes in HAM and KAM of the affected leg Furthermore, as with walking, bipedal standing also showed an asymmetric mechanical load distribution in patients with unilateral hip osteoarthritis. Overall, the findings suggest the need for preventive therapy concepts that focus not only on walking but also on optimizing stance towards a balanced load distribution of both legs.